Building Local Governance: Participation and Elite Capture in Slum‐upgrading in Kenya. Issue 2 (15th January 2014) - Rigon, Andrea
ABSTRACT Community and democratic participation are still an essential component of current mainstream development interventions. However, elite capture seriously undermines the outcomes of development projects. This article analyses the effects on (in)equality of the implementation of policies that are technically participatory, in the context of an internationally‐funded urban development programme in Nairobi, which was implemented in the aftermath of the post‐election violence of 2007–2008. Ethnographic data reveal how the institutionalization of pre‐existing power imbalances between landlords and tenants is accomplished through the creation of structures of community governance and 'participatory enumeration'. The article concludes that without the resources to challenge powerful interests within the settlement, the programme is likely to worsen the condition of a large section of the residents. In the context of strong pre‐existing inequalities and conflict, participation needs careful management and firm external agency to achieve genuine social transformation.